Characterization of Immune Aging in the Japanese Medaka (Oryzias latipes) - Elizabeth DiBona; Joseph L. Humble; Daniel Duran; Doris Wai Ting Au; Frauke Seemann (Fishes)
The prevalence of chronic inflammation increases with age and may be aggravated by environmental exposures. Similarly, during immune aging, inflammatory disease incidence increases as protective immunity decreases. To better understand disease and exposure risks, an immune aging model outlining key changes in immune function is crucial. Utilizing the lowest possible vertebrate class, we propose the Japanese medaka (Oryzias latipes) as a model to investigate sex-specific immune aging including changes in immune gene expression, leukocyte profiles, and organismal level immune response. Evaluating the expression of immune initiators (CRP, TLR5-s, TLR5-m, TCRb, and MHCII), immune mediators (MYD88, Nf-kß, C3, and IL1b), and immune effectors (LYZ and C8) in concomitance with alterations in leukocyte populations and host resistance to pathogens will inform about immune competence across ages. The data presented here demonstrate a critical decrease in the expression of immune initiators (CRP, TLR5-soluble, TCRb, and MHCII), mediators (MYD88, Nf-kß, C3, and IL1b), and effector (LYZ) in both females and males after 11 months post hatching (mph). Interestingly, both sexes displayed an upregulation for the immune effector, C8, during this older life stage (11–13 mph). Gene expression profiles for both sexes at the most elderly age (20 or 23 mph) appear to revert to a younger profile of expression indicating a second change in immune function during aging rather than a steady decline. Significant changes in leukocyte populations were observed in both male and female medaka after peaking sexual maturation at 3 mph. Organismal level immune competence data revealed male medaka at the elderly age to be more vulnerable than their female and younger male counterparts while no differences were observed in females based on age. Together, these data provide a holistic profile for immune aging in medaka, a useful tool for future immunological studies considering age as a factor influencing disease susceptibility.